EXPLORATORY STUDY OF THE CO-CREATION OF VALUE FOR LUXURY BRAND OWNERS: USING SOCIAL MEDIA - Pattie, Ben (2011)
The rapid increase in the uptake of social media has presented brand owners with a new channel for marketing communications. However, the adoption of social media by luxury brand owners is a topic that generates much debate because of the conflict between the accessibility this generates and the luxury requirement to maintain exclusive appeal. Moreover, the current academic literature suggests that social media applications provide a virtual platform for firms and customers to engage in processes of co-creation; however direct links in the literature are not explicit. This exploratory study corrects the gap in the literature, simultaneously analysing the notions of social media and co-creation in the context of the luxury brand. Using a netnography research method and applying a case study approach, this qualitative study of five of the most acclaimed luxury brands for social media marketing, offers new insights into how luxury brand owners can use social media for co-creation purposes. More specifically, this study establishes the types of value luxury brand owners and customers can co-create using social media. Additionally, new recommendations are made for luxury brand owners relating to issues associated with managing the processes of co-creation when using social media. Finally, the study offers further insight into the extent to which social media applications can be used to build and support online luxury brand communities.